2009
DOI: 10.1016/j.jcrc.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bedside open lung biopsies on the management of mechanically ventilated immunocompromised patients with acute respiratory distress syndrome of unknown etiology

Abstract: Background: Open lung biopsy (OLB) is helpful in the management of patients with acute respiratory distress syndrome (ARDS) of unknown etiology. We determine the impact of surgical lung biopsies performed at the bedside on the management of patients with ARDS. Methods: We reviewed all consecutive cases of patients with ARDS who underwent a surgical OLB at the bedside in a medical intensive care unit between 1993 and 2005. Results: Biopsies were performed in 19 patients mechanically ventilated for ARDS of unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
2
26
0
2
Order By: Relevance
“…The operating ARDS definitions have been used in confrontations with lung histology in two autopsy studies. In previous studies on OLB in ARDS, the rates of DAD ranged between 7 [20] and 60 % [19], but most of these studies were performed in the early stage of ARDS [6,[19][20][21][22], making the comparison with the present study difficult. When 284 patients with ARDS risk factors were analyzed, sensitivity was found to be 76 % and specificity 75 %.…”
Section: Relevance Of the Present Studymentioning
confidence: 92%
“…The operating ARDS definitions have been used in confrontations with lung histology in two autopsy studies. In previous studies on OLB in ARDS, the rates of DAD ranged between 7 [20] and 60 % [19], but most of these studies were performed in the early stage of ARDS [6,[19][20][21][22], making the comparison with the present study difficult. When 284 patients with ARDS risk factors were analyzed, sensitivity was found to be 76 % and specificity 75 %.…”
Section: Relevance Of the Present Studymentioning
confidence: 92%
“…An open biopsy may trigger acute attacks in patients with idiopathic pulmonary fibrosis [10]. Given the restrictions when performing an open-lung biopsy in patients with acute and severe respiratory distress, a limited number of studies have examined biopsy data from this patient group [11–13]. Thus, forensic autopsies and the examination of DAD prevalence may be an alternative area of research [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic yield of OLB, which does not specifically address solid organ transplant patients, ranges between 34% and 100% (16,17,19,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In solid organ transplant patients, Defranchi et al reported that 29% had a change in clinical management as a result of the OLB findings (16).…”
Section: Discussionmentioning
confidence: 99%